Actors and communities of social debate - Bañón, Antonio (2023)
Social debate is a hypergenre that allows for the exchange of public discourses on socially relevant topics, as has been developing for years in relation to health and illness, including migration processes. The necessary interrelation of superstructural (actors, genres and contextual elements), macrostructural (thematic dynamics), mesostructural (argumentation) and microstructural (phonic, graphemic, morphological or lexical-semantic elements that regulate the intensity of discourse) elements is highlighted if discourse analysis is to provide an ambitious response to very complex social problems. There are categories which, in these earlier models, called for a more detailed analysis. The types of actors who communicate and their groupings are good examples. This article offers a new systematisation of actors (and actions) and proposes a new unit of analysis: the social discussion community. The following types of social actors are presented and exemplified: hypoactors, microactors, mesoactors, macroactors, superactors and hyperactors. It also presents types of social discussion community groupings: precommunity, subcommunity, community, commonwealth, supracommunity and hypercommunity. Finally, the description of actions associated with direct intervention in the problems discussed and their possible solution is expanded.